An Effective Classification Method for Facebook Data - Fatih Ertam (International Journal of Applied Methods in Electronics and Computers, 2017)
Today, the use of the internet has become very common. One of the most important reasons for its widespread use is social media tools. Especially Facebook has a very important place in social media tools. For this study, classification was done by using Facebook data. Classifications made by artificial learning algorithms on a previously used data set are compared with accuracy values and learning times. For this purpose, support vector machines (SVM), extreme learning machines (ELM) and K nearest neighbor (kNN) approaches are compared. For the study, SVM and ELM algorithms were observed using different activation functions. For the study with KNN, different K values were tested with different distance metric calculation methods. In the classification approach with ELM, it was observed that higher accuracy values were reached in a shorter time. In addition, Receiver Operating Characteristic (ROC) curves are plotted for the classification in which the best values are obtained for each algorithm.